School Certification Assessment Process: Implications to Quality Assurance in the Basic Education System - Luis, Criselda L; Cruz, Ruth A Ortega-Dela (Universitas PGRI Madiun, 2024)
The school certification assessment process plays a crucial role in ensuring the quality of education provided by educational institutions. However, this process is not without its challenges. This study explores some of the key challenges faced during school certification assessments and discusses some implications for quality assurance in a developing country. A survey research design using quantitative and qualitative methods was conducted with 40 junior high school faculty, staff, and administrators from four selected Education Service Contracting (ESC)-participating schools in San Pablo City, Laguna, Philippines. An e-survey questionnaire was used online through Google Forms. Findings revealed that the recertification process presents significant challenges for ESC-participating schools, and some did not achieve the certified status because they did not meet the Department of Education (DepEd) minimum standards and Private Education Assistance Committee (PEAC) certification requirements. In addition, there is a lack of government support and incentives for the schools. The study recommended specific ways to address the issues encountered. By addressing these challenges, we can enhance the effectiveness and credibility of the certification process, ultimately leading to improved educational outcomes.